2018
DOI: 10.1136/bcr-2017-223447
|View full text |Cite
|
Sign up to set email alerts
|

Angiolymphoid hyperplasia of external ear treated with intralesional radiofrequency ablation

Abstract: A 21-year-old woman presented with multiple erythematous to skin-coloured dome-shaped firm papules and plaques over the right ear concha and external auditory canal for 1 year. It was associated with occasional itching and bleeding. Her main concern was cosmetic disfigurement. Biopsy showed presence of multiple proliferating blood vessels lined by plump epithelioid endothelial cells surrounded by dense infiltrate of lymphocytes, histiocytes and eosinophils. Other routine investigations were within normal limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This monotherapy technique of delivering intralesional radiofrequency using iv cannula has been used in other dermatological conditions like lymphangioma circumscriptum, capillary venous malformations, hidradenitis suppurativa as reported by Subadarshani et al, 6 in angiolymphoid hyperplasia of ear as reported by Yadav et al 7 and in papular acne scars over face by Sanke et al 8 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This monotherapy technique of delivering intralesional radiofrequency using iv cannula has been used in other dermatological conditions like lymphangioma circumscriptum, capillary venous malformations, hidradenitis suppurativa as reported by Subadarshani et al, 6 in angiolymphoid hyperplasia of ear as reported by Yadav et al 7 and in papular acne scars over face by Sanke et al 8 …”
Section: Discussionmentioning
confidence: 98%
“…This monotherapy technique of delivering intralesional radiofrequency using iv cannula has been used in other dermatological conditions like lymphangioma circumscriptum, capillary venous malformations, hidradenitis suppurativa as reported by Subadarshani et al, 6 in angiolymphoid hyperplasia of ear as reported by Yadav et al 7 and in papular acne scars over face by Sanke et al 8 Also Janahi et al has reported an another combination therapy for the treatment of firm and resistant keloids by using fractional ablative laser with a combination of topical application and intralesional injection of TAC with a promising approach. 9 The major limitation of our study was study did not include controls and there may be the possibility of observer's and patient bias during POSAS calculation.…”
Section: Methodsmentioning
confidence: 99%
“…A single sitting of intralesional radiofrequency ablation led to almost complete resolution of ALHE of the ear with no recurrence at three-month follow-up [ 8 ]. However, we did not have this option available in our hospital to implement it on our patient.…”
Section: Discussionmentioning
confidence: 99%